Impact of the COVID-19 pandemic on sex-related disparities in cystic fibrosis healthcare utilization and outcomes: A population study - Jason Weatherald; Chuan Wen; Heather Sharpe; Winnie M. Leung; Paul E. Ronksley; Jeffrey A. Bakal; Michael K. Stickland; Douglas P. Gross; Grace Y. Lam (PLoS ONE, 2026)
Background The COVID-19 pandemic disrupted healthcare utilization and access for many, with persons living with pre-existing pulmonary conditions like cystic fibrosis (pwCF) having been the most impacted. PwCF appeared to have improvements in lung function and reduction in pulmonary exacerbations during the pandemic. However, it is not clear if general healthcare utilization beyond CF centers were also reduced and whether there existed any sex-based differences in health outcomes during the pandemic. Our objective was to use population-level administrative data to gain a comprehensive understanding of healthcare utilization and outcomes for pwCF pre- compared to post-COVID. Methods A retrospective provincial-level analysis was conducted using linked administrative datasets from a single-payer health jurisdiction in Alberta, Canada. We measured hospitalization, emergency department and outpatient visits in pwCF 18 months before and after March 12, 2020. Subgroup analysis was undertaken to differences between sexes. Results Acute care encounters (including general emergency department [ED] visits and hospitalizations) for pwCF declined during the pandemic. There was a trend towards an increase in outpatient primary care and specialist clinics (both virtual and in-person) in the post-COVID period. Mortality rate was largely unchanged during the pandemic. CF females and males experienced the same relative change in healthcare utilization during the pandemic with a greater reduction in ED visits by CF females. Conclusion PwCF accessed acute care resources less but females experienced a greater drop in ED visits despite similar hospitalization rates as males, raising the possibility that females with CF experienced a disproportionate barrier to accessing acute care.